Acute Ischemic Stroke in Relation of COVID-19 - Ali, Md Amir; Islam, Aminul; Chowdhury, R U; Islam, Sheikh Shahidul; Aliuzzaman, Md; Mukherjee, Sudipta Kumar; Ashrafee, Pariza (Bangladesh Journal of Neurosurgery, 2022)
Introduction: In 21st century, the miserable medical condition is still Corona virus disease 2019 (COVID-19). It is such a pandemic disease that was unexpected by this generation. The culprit organism by which the whole world embraced is severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Involvement of respiratory system with such notorious microorganism enhances hypoxaemia. Hypoxia and other procoagulant including platelet increment in COVID-19 accelerate ischemic stroke. Our aim is to observe the effects of COVID-19 on pro-coagulation and platelet dysfunction that enhance ischemic stroke. Materials and Methods: Total 108 patients were diagnosed as SARS-CoV-2 and had been first time reported & were admitted in Combined Military Hospital (CMH) Mymensingh, within 1st March 2020 to 18th May 2021. Total 108 patients were randomly selected and divided into two groups one with simple form and another with severe disease, procoagulation-morbidities, coagulation disorder- specially Ddimer positive COVID-19 disease. Out of those 108 patients simple variety of COVID- 19 were 56 (51.85%) and Complex COVID-19, 52(48.15%) patients. Diagnosis was done based upon details patients’ history, clinical examination, haematological test, radiography of chest and confirmed by Reverse Transcription Polymerase Chain Reaction (RT-PCR). Results:Out of the 108 COVID-19 patients, males were 88(81.48%); females were 20(18.52%) and males were predominant.COVID-19 Incidence among the age group; 10-19 years 07(6.48%), 20-29 years 38(35.19%) and 30-39 years 34(31.48%), 40-49 years 20(18.52%), 50 years or more 9(8.33%) in number and mostly affected in young adult &adult. Regarding Procoagulant; D-dimer positive 13(59.09%), Thrombocytosis 6(27.27%) and Mixed 3(13.64%) patients and mostly D-dimer positive. Out of 108 patients; Simple 56 (51.85%) and Complex COVID-19, 52(48.15%) patients. Of complex COVID-19 that prone to ischemic stroke; Procoagulant 22(42.31%), CVS disorder 10(19.23%), DM 5(9.62%), Severe Pulmonary lesion 8(15.38%), Multiple-comorbidities 7(13.46%) patients and Procoagulant is predominant. Only 3(2.78%) were diagnosed as Acute Ischemic stroke and treated promptly. Amongst 108 patients, 4(four) patients were died ; 1st one with heart failure , 2nd one with HTN,MI , 3rd one with HTN, Old haemorrhagic stroke and last one with CKD,ARDS and most of them are above 50 years of age. And fortunately no patient had died with ischemic stroke as preventive measure with anticoagulant with or without thrombin inhibitor utilized for complex COVID-19. Conclusion: Coagulum is the crucial factor of ischemic stroke.COVID-19 can produce severe pulmonary lesion followed by hypoxia to polycythemia, prothrombotic state and thrombocyte dysfunction. This procoagulation enhance acute ischemic stroke. Bang. J Neurosurgery 2021; 11(1): 18-24